Faktor-Faktor Yang Berhubungan Dengan Kejadian Tuberkulosis Pada Anak - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT Background: Still tuberculosis (TB) is the main problem for most of world society, especially in developing countries